« L’étrangeté vocalique » dans quelques nouvelles de Flannery O’Connor et de Barry Hannah - Claudia Desblaches (Revue LISA)
Starting from Steven Connor’s definition of “the vocalic uncanny” as thwarted or imperfect utterance or “the conflict of embodiment and meaning” (in Myth, Modernity and the Vocalic Uncanny), this article attempts to identify the different manifestations of strangeness or the uncanny, notably strange vernacular words or the repressed voice which surges unexpectedly in simple letter changes. Our survey is reinforced by the observation of the strange voices of many characters in Flannery O’Connor’s and Barry Hannah’s short stories. All these symptoms of the “vocalic uncanny” tend to show that any vocal change has a metaphorical impact, thus encouraging the reader to discover hidden meanings in sounds, graphical errors or “strange and alien occurrences”. Indeed, as Julia Kristeva argues in Le Langage, cet inconnu, there are “acoustic images” in both writers’ stories, which disturb representation and create a network of indeterminate referents. Finally, one may hastily retain the impression of obscurity and abstruseness from both writers, but this eariness / eeriness contributes to the main quality of their short stories (their poetic virtues). Even if Barry Hannah’s strangeness obliges the reader to decipher and decode abstruse references and passages, his fascinating writing relies precisely on that strangeness and difficulty. As for F. O’Connor, the strangeness of her voice simply mirrors the mystery of God’s presence.